Aqueous phase synthesis of polysubstituted pyrimidines/pyrrolidines catalyzed by β-cyclodextrin - Shankar, Jilla; Satish, Gaddam; Ramesh, Katla; Durga, Nageswar Yadavalli Venkata (European Journal of Chemistry, 2014)
Highly substituted pyrimidine/pyrrolidine derivatives were synthesized for the first time in water under neutral conditions by the reaction of aromatic amines, dimethyl/diethyl acetylene dicarboxylates, formaldehyde mediated by β-cyclodextrin (β-CD) in good to excellent yields. β-Cyclodextrin can be recovered and reused without any loss of catalytic activity. The β-Cyclodextrins employed were inexpensive and readily available when compared to other types of cyclodextrins (α, γ).